Establishing norms for kinesthetic coordination tasks in 6-year-olds in the Mangaung, Motheo District - Bonafede, Carmen (University of the Free State, 2021)
Background: A well-functioning proprioceptive system and overall kinesthetic coordination is foundational to six-year-old children’s movement coordination abilities. The age of six is a crucial time in children’s developmental years, and in South Africa this is the age when they enter the formal school setting. Intact proprioception and kinesthetic coordination are therefore essential for the six-year-old South African. Several intrinsic and extrinsic factors such as gender, hand dominance and socio-economic status (SES) can influence the kinesthetic coordination abilities of six-year-old children. Norms for kinesthetic coordination testing is not available and testing is either inaccessible to everyone and/or very costly from this the main aim of the study was formed. Aims: The first aim of this study is to establish norms for kinesthetic coordination tasks in six-year-old children in the Mangaung, Motheo district and, secondly to establish if kinesthetic coordination differences occur in six-year-olds regarding school quintiles, gender and hand dominance. Setting: The participant group consisted of N=193 six-year-old children of which 97 were boys and 96 were girls, with an average age of 6.46 years (0.27). Participants forming part of this dissertation’s study population were from different quintile schools (one to five) in the Mangaung, Motheo district. Methods: Five kinesthetic coordination tasks (Angels-in-the-snow, Rhomberg, finger-to-nose, shoulder-level-arm raise and force perception) were identified and used to establish norms. Using these norms associated with the five identified kinesthetic coordination tasks differences in school quintiles, gender and hand dominance were studied. Analysis of the study was largely descriptive of nature and norms were calculated using frequencies and percentages. Differences between school quintiles were calculated using the Cochran-Mantel-Haenszel (correlation) chi-square test, and gender and hand dominance differences were calculated using the nonparametric Wilcoxon Two-sample test. Cohens d effect sizes were used to calculate practical significance where applicable. Results: Norms were successfully established for the five kinesthetic coordination tasks. Angels-in-the-snow norms was set at six to ten successful repetitions, Rhomberg norms at 22 – 30 seconds of balance, norms for finger-to-nose for the left and right hand was set at two to three successful repetitions. Norms for shoulder-level-arm-raise for the preferred arm and both arms were set at two to four successful repetitions and for the non-preferred arm at one to four successful repetitions, and lastly for force perception the norm was seen as being able to correctly identify in which hand the heavier weight was placed. Using these norms, it was evident that children in higher SES schools outperformed children in lower SES schools in most of the tasks, except for the Rhomberg task. No significant gender differences in kinesthetic coordination abilities were observed; however, girls mainly outperform boys, with the exception of the shoulder-level-arm-raise task. No practical significance was seen in the Angels-in-the-Snow and Rhomberg tasks regarding gender and preferred arm, although a practical significance was seen for finger-to-nose regarding the left hand and none for gender. For shoulder-level-arm-raise a small practical effect was seen regarding the right hand and again none for gender. No calculations were done for force perception. Conclusions and recommendations: Norms for kinesthetic coordination tasks in six-year-old children were successfully established. Kinesthetic coordination abilities are to an extent influenced by school quintile statuses, gender and hand dominance, as differences occurred. It is recommended that Kinderkineticists in practice use the established norms of the five kinesthetic coordination tasks to identify children with possible proprioceptive functioning or kinesthetic coordination backlogs. This can be followed by the implementation of a programme that is specifically tailored to each child’s individual kinesthetic coordination backlogs. Future research on a larger sample size, in different provinces of South Africa, and on children of different age ranges is advised. It is also recommended that the reliability and validity of the five task items be established in future research.
Dissertation (M.A. (Human Movement Sciences))--University of the Free State, 2021
Keywords: Proprioception; Kinesthetic coordination; Socio-Economic Status (SES); Gender; Hand dominance; Bilateral coordination; Quintiles; Norms